Information literacy of secondary school students in Singapore - Ang, Joo Kim (2008)
This study sets out to explore the needs of secondary school students in Singapore for information literacy and information skills, and how the latter are incorporated in the school curriculum. More specifically, it attempts to find out teachers' views of students' needs for information literacy; teaching approaches, methods and techniques for imparting information skills; how information literacy programmes are integrated into the school curriculum; how school/teacher librarians and classroom teachers collaborated; and the attitudes of the school and teachers towards developing information literacy.